Design, Synthesis, Molecular Docking, in silico ADME Assessment of Pyrrole-Based Heterocyclic Amino Acid Derivatives as Potential Anticonvulsant Agent - Alam, Md Shamsher; Albratty, Mohammed; Alhazmi, Hassan Ahmed; Najmi, Asim; Zoghebi, Khalid; Makeen, Hafiz Antar; Saleh, Safaa Fathy; Kirdasy, Ahmed Farag El; Kochikuzhyil, Benson Mathai (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Epilepsy is a neurological disorder characterized by anomalous brain activity, convulsionsandoddbehaviour.Tenpyrrolecarbohydratebasedanalogues(Va-Vj)weresynthesized with amide as intermediate in the current research with the goal of reducing convulsions and seizures. Materials and Methods The newly developed compounds were synthesized. Numerous methods (IR, NMR, mass, elemental analysis, etc.,) were used to characterize these substances. Several models were used to test each of these molecules for anticonvulsant activity. By using the rotarod and ethanol potentiation techniques, neurotoxicity was also evaluated. The study meticulously examined each parameter and showed ADME predictions for each of the 10 congeners that were produced. In addition, studies on molecular docking employed the GABA-A target protein. Results Anticonvulsant screening results identified compounds Ve, Vd, Vc and Va as the most efficacious of the series. All synthesized equivalents largely passed the neurotoxicity test. The results of molecular docking revealed significant interactions at the active site of GABA-A with Ile C:242, Asp C:424, Phe D:307, Arg C:250 Trp C:241 and Phe C:240 and the outcomes were good and in agreement with in vivo findings. Conclusion The study’s findings showed that some substances had promising anticonvulsant properties that were comparable to those of the standard drug. The highly active novel anticonvulsant analogues may therefore represent a possible lead and additional studies may result in a potential new drug candidate.
Keywords: N-glycosides; Carbohydrate; Anticonvulsant activity; Pyrrole; ADME